2013
DOI: 10.1121/1.4800420
|View full text |Cite
|
Sign up to set email alerts
|

Contribution analysis of vehicle exterior noise with operational transfer path analysis

Abstract: Vehicle development regarding the emitted exterior noise is a challenging task. In addition to stringent legal requirements to reduce noise exposure, also high expectations of the sound quality have to be considered during the development process. In order to manipulate the vehicle exterior noise in a manner more efficient than trial and error, knowledge about the vehicle's sound sources and their contributions to the overall noise is essential. In order to analyze the contributions of the several sound source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The HVAC components were considered based on the contributions estimation as described by Thawani et al The noise measurement was carried out using a microphone (BSWA, type: MA231). The microphone was placed at a distance of 10 cm from the HVAC components with an offset of 10 cm, as experimented by Putner et al (2013). For the vehicle system in Fig.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…The HVAC components were considered based on the contributions estimation as described by Thawani et al The noise measurement was carried out using a microphone (BSWA, type: MA231). The microphone was placed at a distance of 10 cm from the HVAC components with an offset of 10 cm, as experimented by Putner et al (2013). For the vehicle system in Fig.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…The influence of the correlation between the input reference points on the accuracy of the transfer function was explored and the results showed that the more accurate transfer function can be obtained by CTC. Putner et al [14,15] used the artificial excitation on the vehicle, analyzed and found out the contribution of the noise sources. Roozen and Leclère [16] used hammer strikes as input signals of OTPA method, which could reduce the crosstalk between the input signals and save the time compared with the actual input condition.…”
Section: Introductionmentioning
confidence: 99%
“…In [9], the acoustic transfer path analysis described above was used to estimate tyre noise and was proven very practical due to the small number of microphones needed close to the tyres to capture the near field spectra. This work served as the basis for a few similar studies [10][11][12] utilising the inverse methodology, while an alternative power-based approach was introduced in [13] and was shown to produce good results. A very similar concept was also used in [14,15], where the need for regularisation in the inverse method was first introduced.…”
Section: Introductionmentioning
confidence: 99%